Deciphering Spinal Endogenous Dopaminergic Mechanisms That Modulate Micturition Reflexes in Rats with Spinal Cord Injury - Hou, Shaoping (eNeuro, 2021)
Spinal neuronal mechanisms regulate recovered involuntary micturition after spinal cord injury (SCI). It was recently discovered that dopamine (DA) is synthesized in the rat injured spinal cord and is involved in lower urinary tract (LUT) activity. To fully understand the role of spinal DAergic machinery in micturition, we examined urodynamic responses in female rats during pharmacological modulation of the DA pathway. Three to four weeks after complete thoracic SCI, the DA precursor L-DOPA administered intravenously during bladder cystometrogram (CMG) and external urethral sphincter (EUS) electromyography (EMG) reduced bladder overactivity and increased the duration of EUS bursting, leading to remarkably improved voiding efficiency. Apomorphine (APO), a non-selective DA receptor (DR) agonist, or quinpirole, a selective DR(2) agonist, induced similar responses, whereas a specific DR(2) antagonist remoxipride alone had only minimal effects. Meanwhile, administration of SCH 23390, a DR(1) antagonist, reduced voiding efficiency by increasing tonic EUS activity and shortening the EUS bursting period. Unexpectedly, SKF 38393, a selective DR(1) agonist, increased EUS tonic activity, implying a complicated role of DR(1) in LUT function. In metabolic cage assays, subcutaneous administration of quinpirole decreased spontaneous voiding frequency and increased voiding volume; L-DOPA and APO were inactive possibly because of slow entry into the CNS. Collectively, tonically active DR(1) in SCI rats inhibit urine storage and enhance voiding by differentially modulating EUS tonic and bursting patterns, respectively, while pharmacologic activation of DR(2), which are normally silent, improves voiding by enhancing EUS bursting. Thus, enhancing DA signaling achieves better detrusor-sphincter coordination to facilitate micturition function in SCI rats.